(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Exposure of humans and wildlife to pollutants released in the environment is a centre of attention nowadays. Many of these chemicals (generally referred to as environmental pollutants) have been shown to interfere with normal hormonal signalling and biological functions, leading to reproductive disorders or infertility, which has been a matter of concern within the recent decades. The present paper reviews adverse effects of these toxicants on mammalian testes, with emphasis on alteration of steroidogenesis, spermatogenesis, and histopathological effects. From the publications reviewed, it appears that environmental toxicants, especially heavy metals and organic chemicals of synthetic and microbiological origins, disrupt hormone production and action in the mammalian testes. Endocrine disruption leads to disorders of testicular function and thereby compromises the normal p henotypic development of male sexual characteristics, initiation and maintenance of spermatogenesis. The toxicants also induce impairment of testicular cells function, testicular histology, and sperm cells function directly. The release of the toxicants in the environment is still ongoing, despite alarming quantities that already exist in the atmosphere. If appropriate measures are not taken, their impact on the male reproductive function and especially on testicular function will be more serious.The present examination was an endeavor to assess1.The impacts of aluminum andor arsenic on the structure and elements of male reproductive organs.2.Withdrawal considers on reversibility of aluminum and arsenic prompted impacts.3.The conceivable remedial impacts of β-carotene after oral organization for relief of aluminum andor arsenic toxicity.